2002
DOI: 10.1023/a:1016017224003
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction in Sepsis: Evidence from Bacteraemic Baboons and Endotoxaemic Rabbits

Abstract: Mitochondria, that provide most of the ATP needed for cell work, and that play numerous specific functions in biosyntheses and degradations, as well as contributing to Ca2+ signaling, also play a key role in the pathway to cell death. Impairment of mitochondrial functions caused by mutations of mt-genome, and by acute processes, are responsible for numerous diseases. The involvement of impaired mitochondria in the pathogenesis of sepsis is discussed. By means of the skinned fiber technique and high resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Performing spectrophotometric measurements of rat left ventricular cardiac tissue after echinocandin treatment, we were not able to detect any altered mitochondrial enzyme activity (12). Previous studies on septic cardiomyopathy demonstrated the importance of mitochondrial dysfunction and reduced ATP generation (22,23). Moreover, studies using isolated cardiomyocytes found that endotoxins alter or suppress the L channel-dependent calcium flow, possibly through changes in autonomic regulation of this channel (24,25).…”
Section: Discussionmentioning
confidence: 63%
“…Performing spectrophotometric measurements of rat left ventricular cardiac tissue after echinocandin treatment, we were not able to detect any altered mitochondrial enzyme activity (12). Previous studies on septic cardiomyopathy demonstrated the importance of mitochondrial dysfunction and reduced ATP generation (22,23). Moreover, studies using isolated cardiomyocytes found that endotoxins alter or suppress the L channel-dependent calcium flow, possibly through changes in autonomic regulation of this channel (24,25).…”
Section: Discussionmentioning
confidence: 63%
“…Therefore these mitochondria are an excellent model for the study of AK-induced dynamic compartmentation within the IMS. In the presence of 10 yo (w/v) dextran M20 or BSA, approximately 64 yo of the maximal ADP flux from mt-AK to oxidative phosphorylation was not accessible to the extramitochondrial ADP scavenger pyruvate kinase [9,17,20,21]. In the absence of macromolecules this portion was only 34 yo [20,21].…”
Section: Awhk Systemmentioning
confidence: 99%
“…Based on the experimental data it was possible to perform a simulation by means of a mathematical model, including diffusion terms [7,8]. Using such models diffusion rate constants six times lower than in the presence of dextran could be estimated (B. Korzeniewski and F. N. Gellerich, unpublished work).…”
Section: Rate-dependent Concentration Gradients and Dynamic Adp Compamentioning
confidence: 99%
See 1 more Smart Citation
“…Focal ischemic/hypoxic changes have also been demonstrated in the endometrium of women with IUA [6]. Cellular oxygen delivery is well known to be most utilized by the mitochondria, which is the main intracellular energy source that is necessary for normal cellular function and metabolic homeostasis through oxidative phosphorylation [7]. It is suggested that the metabolic dysfunction of the mitochondria in endometrial cells may be an important factor that causes IUA.…”
Section: Introductionmentioning
confidence: 99%